The Effect of Video-Based Education Strategies on Early Mobilization Compliance of Post Sectio Caesarea Mothers in the Lotus Room of Primaya Sukabumi Hospital - Devia Widianty; Erna Safariyah; Egi Mulyadi; Irawan Danismaya (Health Research Journal of Indonesia, 2026)
After a cesarean section, many mothers experience discomfort in the incision area and limited mobility, which can increase the risk of infection, delay uterine involution, and impair recovery. Early mobilization plays a crucial role in accelerating the healing process and preventing complications, but patient compliance remains low due to limited understanding. Video-based education is an innovative alternative that can increase patient engagement and understanding. This study aimed to determine the effect of a video-based early mobilization strategy on mothers' compliance with early mobilization after cesarean section in the Lotus Ward at Primaya Hospital, Sukabumi. This study used a quasi-experimental design with a control group and pre-post test measurements. A sample of 36 respondents, divided into 18 in the intervention group and 18 in the control group, was selected through purposive sampling. The intervention group received video-based education, while the control group received no intervention. Data were analyzed using the Wilcoxon Signed-Rank test at a significance level of 0.05. There was a significant increase in early mobilization compliance scores in the intervention group after receiving video-based education (p < 0.05), while the control group showed no significant change. Video-based education strategies are effective for increasing early mobilization compliance among mothers after cesarean section. Hospitals are advised to integrate video education into their postoperative care programs to support optimal patient recovery.